Effect interfacial size and multiple interface on electromagnetic shielding of silicon rubber/carbon nanotube composites with mixing segregated particles. (15th July 2022) - Yang, Dian; Tao, Jun-Ru; Yang, Yi; He, Qian-Ming; Weng, Yun-Xuan; Fei, Bin; Wang, Ming
Highlights: EMI SE of the composites increased with decreasing size of segregated particles. Small segregated particles had high EMI SE due to high volume exclusion effect. High interfacial polarization and scattering were also important to high EMI SE. Micro/micro and nano/micro mixed segregated particles further enhanced EMI SE. Interface regularity related to EMI SE of composites with mixed micro-particles. Abstract: Controllable distribution of conductive fillers in CPCs, such as segregated distribution, has been applied to improve electromagnetic interference (EMI) shielding effectiveness (SE). In this study, the effect of size and size distribution of segregated particles on electromagnetic shielding performance was explored in polydimethylsiloxane/multi-walled carbon nanotube composites (PDMS/CNT) via regulating the diameter of silicon dioxide (SiO2 ) particles. Through the addition of segregated SiO2 particles, the volume exclusion effect was introduced into the composites to construct dense conductive networks. With decreasing the size of segregated particles, the EMI SE of the samples enhanced on a whole, because of the increase of interfaces. Furthermore, the SiO2 particles with different diameters mixed to create the composites with multiple interfaces. Micro-micro segregated particles exhibited a synergistic effect when the diameters matched with each other. Nano-micro segregated particles enhanced interfacial polarization to enhance EMI shielding performance, although the conductive networks were damaged by the adhesion of nano-particles on CNTs. On a whole, the addition of single and mixed segregated particles could achieve excellent microwave shielding performance through the volume exclusion effect, the interface regularity, the multiple scattering at the interface, and the mutual interference efficiency.